Integration SERVQUAL and QFD For Improved Quality of Service (Case Study: Mass Transport Trans Padang) - Henny Yulius; Irsan Irsan; Wira S Syukma (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
This study was carried out to the user community transport services Trans Padang which aims to determine what attributes are needed to identify the perceived service quality as well as how big the gap perceived quality of society as a passenger in order to take specific measures to improve service quality Trans Padang. The method used to analyze the level of inequality is SERVQUAL method and then the consumer voice (Voice of Customers) obtained is integrated with the Quality Function Deployment method of forming a quality home (House of Quality).From the data processing obtained 35 attributes that can identify the quality of service perceived users are divided into 5 dimensions, then of processing SERVQUAL known that there is a gap on the perceptions and expectations of respondents where each attribute has a negative value (-), so that made 13 attempts to improve service quality Trans Padang.In an effort to improve the quality of services Trans Padang, there are several proposed procurement of additional facilities which need to be held soon. Therefore, it is expected that the UPT Trans Padang and Padang City Government to synergize in order to add the necessary facilities.Keywords: House of Quality, Servqual